Characterization of Ceratocystis fimbriata from passion fruits - Firmino, Ana Carolina; Fischer, Ivan Herman; Antonio, Gabriel Leonardi; Novaes, Quelmo Silva De; Tozze Júnior, Hugo José; Furtado, Edson Luis (Instituto Biológico, 2016)
ABSTRACT: Passion fruits (Passiflora edulis ) were found with symptoms of rot in the field, in the city of Tanhaçu, Bahia. After isolating the pathogen associated with this rot, in the present study we aimed to characterize the Ceratocystis isolate from passion fruit for better understanding this pathosystem. Molecular characterization was done based on the region ITS-5.8S rDNA. Pathogenic characterization was carried out for seedlings and fruits of passionflower. Passion fruit colonization was monitored by means of scanning electron microscopy techniques (SEM). DNA analysis of the Ceratocystis isolate from passionflower pointed out that this species belongs to Ceratocystis fimbriata . The inoculated passionflower seedlings showed injury at 30 days post-inoculation, but no inoculated plant showed wilt or died. Considering fruits, no differences were found for lesions caused by this fungus among cultivars, and lesions had average diameters of 1.0 and 2.2 cm at 7 and 11 days, respectively. The analysis using SEM indicated fungus spore germination and penetration in the fruit between 2 and 6 hours post-inoculation. At 12 and 24 hours post-inoculation, fruit colonization was noted both externally and internally, while fruit wall degradation started at 48 hours post-inoculation. At 90 hours post-inoculation, formation of new perithecia was observed inside and outside the fruit. This study complements the available information about the interaction of this fungus with passion fruit.

RESUMO: Frutos de maracujá (Passiflora edulis ) foram encontrados com sintomas de podridão no campo, na cidade de Tanhaçu, Bahia. Após isolamento do patógeno associado a essas podridões, o presente trabalho teve como objetivo realizar a caracterização de um isolado de Ceratocystis de maracujá para melhor compreender esse patossistema. A caracterização molecular foi realizada com base no sequenciamento da região ITS-5.8S rDNA. Realizou-se a caracterização patogênica em mudas e frutos de maracujá. A colonização dos frutos de maracujá foi acompanhada com técnicas de microscopia de varredura (MEV). A análise do DNA do isolado de Ceratocystis mostrou que este pertence à espécie Ceratocystis fimbriata . As mudas de maracujá inoculadas apresentaram lesão 30 dias após a inoculação, e não foram observadas murcha nem morte das plantas inoculadas. Nos frutos não foram constatadas diferenças nas lesões causadas por esse fungo entre os cultivares, com médias de lesões de 1,0 a 2,2 cm de diâmetro, aos 7 e 11 dias, respectivamente. Nas análises realizadas em MEV, foram observadas a germinação dos esporos e a penetração do fungo nos frutos no período entre 2 e 6 horas após a inoculação. Doze e 24 horas após a inoculação foi visualizada a colonização do fruto, tanto externa como internamente, e 48 horas após a inoculação se notou o início da degradação da parede externa da casca do fruto. Noventa horas após a inoculação, observou-se a formação de novos peritécios, tanto na parte interna como na parte externa do fruto. Este estudo vem complementar as informações relacionadas à interação desse fungo com frutos de maracujazeiro.
Caracterização de Ceratocystis fimbriata de frutos de maracujazeiro
Keywords: rot; species; microscopy; podridão; espécies; microscopia